The Effectiveness of Emotionally Focused Couple Therapy on Marital Commitment and Couple Burnout in Infertile Couples - Masomeh Sayadi; Saeed Shahhosseini tazik; Yaser Madani; Masoud Gholamali lavasani (Journal of Education and Community Health)
Background and Objective: Infertility is known as an important stressor threatening the personal, marital, familial, and social stability in all culturesaround the world. The present study aimed to investigate the effectiveness of emotionally focused couple therapy on marital commitment and couple burnout among infertile couples. Materials and Methods: This quasi-experimental study was conducted on 30 infertile couples referring to the private centers of infertility in Qom, Iran, from September 2015 to September 2016, using pretest-postest design with a control group. The study population was selected through purposive sampling technique, and then randomly assigned into the experimental (n=15 couples) and control experimental (n=15 couples) groups. All participants filled out the Dimensions of Commitment Inventory and Couple Burnout Measure. In addition, the couples in the experimental group attended 10 emotionally focused couple therapy sessions performed twice a week. The data were analyzed using the multivariate analysis of covariance and univariate analysis of covariance. Results: The results of the multivariate analysis of covariance showed that emotionally focused couple therapy significantly increased the posttest mean scores of marital commitment and its subscales (i.e., personal commitment, moral commitment, and structural commitment) in the experimental group (P<0.05). Additionally, according to the univariate analysis of covariance, there was a statistically significant difference between the experimental and control groups in terms of the mean scores of the couple burnout at the posttest stage (P<0.01). Conclusion: As the findings indicated, the emotionally focused couple therapy can improve marital commitment and decrease couple burnout.